The Development of Student Grades Information System at SDIT Using Waterfall Model - Sudradjat, Adjat (Politeknik Ganesha Medan, 2019)
As one of the educational institutions, Sekolah Dasar Islam Terpadu (SDIT) must be able to perform the data processing of students' grades well, because it will be used as one of the clear and valid benchmarks to determine student achievement level as learners. The conventional processing system of students' grades require a lot of time and effort for teachers and administrative staff to write down the marks in legs and report books, as well as to recapitulate student grades at the end of the semester. The manual processing of students' grades is also vulnerable to errors that come from inaccuracy in the process, thus affecting the accuracy of data and reduce the level of validity of information generated. The research discusses about the development of computerized academic information system in Sekolah Dasar Islam Terpadu (SDIT) with the aim to provide convenience in processing the data and accelerate the making of reports of achievement of learning. The scope of discussion is to focus on the management of student personal data, student's grades data, student mutation data, to the results of learning achievements through desktop applications using waterfall as the model of development system. With a reliable level of data accuracy, parents can obtain valid reports on student achievement, and SDIT stakeholders can receive strategic information for learning evaluation materials and determine future policy in school teaching and learning activities.